The spread of Entamoeba histolytica infection among children attended the Central Child Hospital in Baghdad city. - A. A. Altikrity, Ilham; A. H. Aljanabi, Marwan (Iraqi Journal of Science, 2023)
A total of 1712 samples of children feces were collected from the Central Child Hospital and examined by direct and concentration methods (zinc sulfate and sucrose) during the period from 01/10/2011 to 19/10/2012. The ages of children were ranging between one month and 15 years.The results of the current study showed that the rate of infection overall was 18.72% and there was a variation in the infection rate between the age groups, reaching the highest incidence in the age group (1- 5 years old). The study indicated also that the percentage of infected males is higher than females, which was 63% and 37% respectively. Also the percentage of infection among children living in the city was 70%, while it was 30% among children living in the rural areas.